1987
DOI: 10.1172/jci113225
|View full text |Cite
|
Sign up to set email alerts
|

Selective binding of somatostatin-14 and somatostatin-28 to islet cells revealed by quantitative electron microscopic autoradiography.

Abstract: Quantitative electron microscopic autoradiography was used for comparing the binding of labeled somatostatin-14 (S-14) and somatostatin-28 (S-28) to islet cells. Monolayer cultures of rat islet cells were incubated with or

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0
5

Year Published

1989
1989
2004
2004

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(23 citation statements)
references
References 22 publications
1
17
0
5
Order By: Relevance
“…These results are in agreement with those of in vitro studies which also demonstrate a relatively greater effect of S-28 on pancreatic B cells (15,19). Recently, an inhibitory effect ofelevated postprandial S-28 levels on pancreatic exocrine secretion has been reported (P. Hildebrand, unpublished observation), so it is likely that the effects of S-28 released during nutrient absorption are not restricted to the pancreatic B-cell.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…These results are in agreement with those of in vitro studies which also demonstrate a relatively greater effect of S-28 on pancreatic B cells (15,19). Recently, an inhibitory effect ofelevated postprandial S-28 levels on pancreatic exocrine secretion has been reported (P. Hildebrand, unpublished observation), so it is likely that the effects of S-28 released during nutrient absorption are not restricted to the pancreatic B-cell.…”
Section: Discussionsupporting
confidence: 91%
“…However, S-28 is the more potent inhibitor of pancreatic B cells and binds to them more avidly than to A cells (15,18,19). Conversely, S-14 binds to and inhibits A cells preferentially (15,19).…”
Section: Introductionmentioning
confidence: 99%
“…Although Moldovan et al [26] reported that insulin secretion is inhibited by an SSTR2A selective analogue in isolated perfused human pancreas, this analogue (DC32-87) has been found not to be SSTR2 selective [5]. Pharmacological data also suggest that different SSTR subtypes are expressed in glucagon and insulin cells in the rat endocrine pancreas, with glucagon secretion being most sensitive to SSTR2-selective analogues and insulin secretion most sensitive to SSTR5-selective analogues in rats [27,28,29]. Recently Kumar et al [16] analyzed SSTR subtype specific expression in human pancreatic islets and found SSTR2 in insulin and glucagon cells, with insulin, glucagon, and somatostatin cells each expressing multiple SSTR isoforms.…”
Section: Discussionmentioning
confidence: 99%
“…Using the technique of quantitative electron microscopic autoradiography, we have previously identified specific binding sites for radioiodinated somatostatin-14 (S-14), '1251-insulin, and '251-glucagon on neonatal islet B, A, and D cells in monolayer culture (22,23). We have extended these observations and now describe the internalization of each radioligand by the three islet cell types.…”
Section: Introductionmentioning
confidence: 88%
“…Monolayer cultures of dispersed islet cells from 3-d-old rats were established in plastic Petri dishes as previously described (22,23). The medium consisted of MEM with 10% heat-inactivated FCS.…”
Section: Methodsmentioning
confidence: 99%